How to solve this application sum?

Asked by  | 30th Apr, 2008, 05:19: PM

Expert Answer:

       α  and  β    are the  zeros of     x2 - x  + 1

    α  + β   =  - coefficient of x term /  coefficient of x2  = 1 / 1 = 1

   αβ  =  constant / coefficient of x2  = 1

  α2  +β2  =  (α  +β   )2 --  2 αβ

                = 12 - 2 * 1

               = - 1

  1 /α  + 1/β  =   α  +  β  / αβ

                     =1  / 1 = 1

    

       

Answered by  | 30th Apr, 2008, 09:27: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.